The Legal Politics of Religious Courts in Indonesia: The Relevance of Islamic Law and Positive Law in Judges’ Decisions - Aji, Ahmad Solikan; Octavia, Nurul Aini (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2025)
Religious Courts in Indonesia are an integral part of the national justice system that has an important role in resolving legal disputes related to Islam. Based on the 1945 Constitution and applicable legal provisions, Religious Courts in Indonesia are run with the aim of providing justice to Muslims in resolving civil and family problems. The legal politics of religious courts are very important to understand how the religious court system works in the context of national law and to see the extent of the relevance and influence between Islamic law and positive law in judges' decisions. The type of research used in this paper is normative legal research, while the research method used is a qualitative research method. Namely research that uses descriptive data in the form of written or spoken language from people and actors that can be observed. The conclusion of this study is that positive law and Islamic law have relevance in judges' decisions, the application of these two legal systems in Indonesia is not always easy. The biggest challenge lies in the integration and harmonization between the two. Overall, positive law and Islamic law are not two separate entities in the Indonesian justice system, but